The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4172/2153-0637.s2-003
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipid Mediated Caveolin-1 Oligomerization

Abstract: We have previously demonstrated an association between the accumulation of the glycosphingolipid globotriaosylceramide (Gb3) and the loss of high molecular weight oligomers in the aortas of α-galactosidase A-knockout mice, a model of Fabry disease. In the present study the molecular basis for the association between glycosphingolipids and caveolin-1 oligomerization was further investigated. Cellular glycosphingolipids were selectively depleted by treatment with a series of sphingolipid synthesis inhibitors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A study of gangliosides from human serum using nano-HPLC-ESI Q-TOF MS also by Kirsch et al . profiled 33 gangliosides and yielded potential biomarkers for pancreatic cancer, illustrating the potential of profiling methods for biomarker discovery 34 .…”
Section: Introductionmentioning
confidence: 99%
“…A study of gangliosides from human serum using nano-HPLC-ESI Q-TOF MS also by Kirsch et al . profiled 33 gangliosides and yielded potential biomarkers for pancreatic cancer, illustrating the potential of profiling methods for biomarker discovery 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Leon Fine and colleagues suggested that chronic kidney hypoxia might be a phenotypic characteristic of models of kidneys with decreased surviving nephrons. 3 During the past decade, several studies of experimental animal models of CKD and the diabetic kidney have verified the earlier prediction that kidney hypoxia does persist in both CKD [4][5][6] and the early diabetic kidney (Figure 1). 7 Why should hypoxia develop as a primary characteristic of or adaptation to CKD and the diabetic kidney?…”
Section: Disclosurementioning
confidence: 57%
“…7 Why should hypoxia develop as a primary characteristic of or adaptation to CKD and the diabetic kidney? Early studies in the subtotal nephrectomy model demonstrated that peritubular capillary rarefaction does occur, 5 raising the question of whether the hypoxia was primarily ischemic in origin. However, this seems less likely given the anatomic arrangement of arterial and venous vessels in the kidney.…”
Section: Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…Lower expression of B3GALT5 may cause the accumulation of Gb4cer or globotriaosylceramide (Gb3cer). Because Gb3cer and other glycosphingolipids are also involved in caveolar-1 oligomerization [ 39 ], their accumulation may affect the sorting and trafficking of caveolae in the membrane, resulting in the function of signaling in fibroblasts. Taken together, the expression profiles of GSLs-GTs suggested their possible roles in “the environmental sensor” in fibroblasts through membrane metabolism.…”
Section: Discussionmentioning
confidence: 99%